2016
DOI: 10.4049/jimmunol.1600089
|View full text |Cite
|
Sign up to set email alerts
|

Features of Human CD3+CD20+ T Cells

Abstract: Monoclonal Abs against CD20 reduce the number of relapses in multiple sclerosis (MS); commonly this effect is solely attributed to depletion of B cells. Recently, however, a subset of CD3+CD20+ T cells has been described that is also targeted by the anti-CD20 mAb rituximab. Because the existence of cells coexpressing CD3 and CD20 is controversial and features of this subpopulation are poorly understood, we studied this issue in detail. In this study, we confirm that 3–5% of circulating human T cells display CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
202
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(233 citation statements)
references
References 33 publications
26
202
1
4
Order By: Relevance
“…Given the increased expression of HLA‐DR on CD3 + CD20 + T cells, it was reasonable to assume that CD3 + CD20 + T cells represented an activated subpopulation and had a potential effector function in patients with psoriasis. In fact, CD3 + CD20 + T cells could produce more proinflammatory cytokines than those in CD3 + CD20 – T cells , and a similar result was also observed in patients with psoriasis. Additionally, we found that CD3 + CD20 + T cells in patients with psoriasis produced higher levels of IL‐17A, TNF‐α and IL‐21 than those in healthy donors, and these cytokine‐production cells showed a significantly positive correlation with the severity of disease.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Given the increased expression of HLA‐DR on CD3 + CD20 + T cells, it was reasonable to assume that CD3 + CD20 + T cells represented an activated subpopulation and had a potential effector function in patients with psoriasis. In fact, CD3 + CD20 + T cells could produce more proinflammatory cytokines than those in CD3 + CD20 – T cells , and a similar result was also observed in patients with psoriasis. Additionally, we found that CD3 + CD20 + T cells in patients with psoriasis produced higher levels of IL‐17A, TNF‐α and IL‐21 than those in healthy donors, and these cytokine‐production cells showed a significantly positive correlation with the severity of disease.…”
Section: Discussionsupporting
confidence: 63%
“…Consistent with these reports, our study also showed that a subpopulation of CD3 + T cells expressed CD20 in the peripheral blood of patients with psoriasis and healthy donors at a similar level, and these cells lacked classical B cell markers CD19 and CD40. However, this subpopulation in patients with psoriasis contained more CD4 + cells and fewer CD8 + cells, whereas more CD8 + cells and fewer CD4 + cells of these cells were observed in healthy donors , suggesting that the constitution of a CD4 + and CD8 + subset in CD3 + CD20 + T cells is altered in patients with psoriasis. In particular, previous studies also showed that CD3 + CD20 + T cells were predominantly CD4 + cells in patients with multiple sclerosis and rheumatoid arthritis ; we speculated that this phenomenon might exist in a variety of diseases.…”
Section: Discussionmentioning
confidence: 92%
“…Emerging data suggest that rituximab has an inhibitory effect on effector T cells and could induce regulatory T cells expansion, which may be related to B cell deprivation resulting in impaired antigen-presenting cells activity and reduced production of co-stimulatory and immuno-modulatory molecules taking part in T cell activation and interactions; besides, it could exert a direct effect on T cells by binding to a specific T cell subset expressing CD20 (35). A recent study confirmed that, CD20 was also expressed on mature medullary thymocytes (36). Therefore, rituximab may intervene T cell development in the thymus by targeting CD20 + thymocytes.…”
Section: Discussionmentioning
confidence: 65%
“…One major difference is on plasma cells: CD20 is absent on mature plasma cells, whereas CD19 is expressed on the majority of plasma cells in the secondary lymphoid organs (such as spleen and tonsils), on all plasma cells in blood, and on more than 50% of plasma cells in bone marrow [39,40]. In addition, CD19 is exclusively expressed on B cells, whereas in contrast, CD20 is also expressed on a subset of CD4 + T cells [41]. Therefore, CD19 has both a broader and a more specific pattern of B-cell expression than does CD20.…”
Section: Rationale For Targeting Cd19 and The Development Of Inebimentioning
confidence: 99%